1999
DOI: 10.1002/(sici)1097-4636(19991215)47:4<516::aid-jbm7>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and inhibitory effect of antibacterial dental resin composites incorporating silver-supported materials

Abstract: Resin composites with antibacterial activity may be useful for preventing the secondary caries frequently seen around restorations. The purposes of this study were to investigate antibacterial light-activated dental resin composites incorporating each of two silver-supported antibacterial materials and evaluate their long-lasting inhibitory effect against Streptococcus mutans. Two types of silver-supported antibacterial materials, Novaron (N) and Amenitop (AM) were used. These antibacterial materials were inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(91 citation statements)
references
References 23 publications
2
81
0
8
Order By: Relevance
“…Previous studies have reported silver compounds added at 10% or greater to dental materials would significantly reduce compressive strength, elastic modulus, and tensile strength. 11,15 Therefore, it seems that nano particles added in low concentrations, as in the present study, would not adversely affect the mechanical properties of composite resins. Discoloration and a change in color to a tone of gray are common problems in all materials containing silver, especially composite resins.…”
Section: Discussionmentioning
confidence: 50%
“…Previous studies have reported silver compounds added at 10% or greater to dental materials would significantly reduce compressive strength, elastic modulus, and tensile strength. 11,15 Therefore, it seems that nano particles added in low concentrations, as in the present study, would not adversely affect the mechanical properties of composite resins. Discoloration and a change in color to a tone of gray are common problems in all materials containing silver, especially composite resins.…”
Section: Discussionmentioning
confidence: 50%
“…15,25,26 Hernández-Sierra et al 27 evaluated the sensitivity of Streptococcus mutans to nano particles of silver (25 nm), zinc oxide (125 nm) and gold (80 nm) and indicated the higher antibacterial properties of nano silver than nano zinc oxide and nanogold; they attributed this results to smaller particle size of nanosilver than nano zinc oxide particles. Concerns exist about the adverse effect of nanoparticle additives on the mechanical properties of composite resins; however, previous studies have reported silver compounds added in 10% concentration or greater to dental materials would significantly reduce compressive strength, elastic modulus and tensile strength.…”
Section: Discussionmentioning
confidence: 99%
“…For efficient prevention or treatment of biofilm infections several systems releasing antibacterial and remineralizing agents have been reported, e.g. fluoride (F − ) [3][4][5][6], calcium (Ca 2+ ) and phosphate (PO 4 3− ) [7][8][9][10] or silver (Ag + ) ions [11,12]. Chlorhexidine (CHX) is a widely applied drug because of its high antimicrobial activity against gram-positive and gram-negative bacteria, fungi and viruses [13].…”
Section: Introductionmentioning
confidence: 99%